2011
DOI: 10.1039/c1pp05074e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight of the photodynamic effect induced by tri- and tetra-cationic porphyrins on Candida albicans cells

Abstract: The photodynamic mechanism of action induced by 5-(4-trifluorophenyl)-10,15,20-tris(4-N,N,N-trimethylammoniumphenyl)porphyrin (TFAP(3+)), 5,10,15,20-tetrakis(4-N,N,N-trimethylammoniumphenyl)porphyrin (TMAP(4+)) and 5,10,15,20-tetrakis(4-N-methylpyridyl)porphyrin (TMPyP(4+)) was investigated on Candida albicans cells. These cationic porphyrins are effective photosensitizers, producing a ~5 log decrease of cell survival when the cultures are incubated with 5 μM photosensitizer and irradiated for 30 min with visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Porphyrin binding to the cytoplasmic membrane and penetration into the yeast cell is a prerequisite for effective ROS production in the yeast cells, which result from effective photoinactivation. In a recent study (43) on tri and tetra cationic porphyrins, it was also shown that these porphyrins bind strongly to C. albicans cells, and the ROS, which is effective in cellular damage, is generated inside the cells. However, the microenvironment in which the yeasts are found during photosensitization can induce failure of this treatment, as found in this study and the above‐mentioned recent study (43).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Porphyrin binding to the cytoplasmic membrane and penetration into the yeast cell is a prerequisite for effective ROS production in the yeast cells, which result from effective photoinactivation. In a recent study (43) on tri and tetra cationic porphyrins, it was also shown that these porphyrins bind strongly to C. albicans cells, and the ROS, which is effective in cellular damage, is generated inside the cells. However, the microenvironment in which the yeasts are found during photosensitization can induce failure of this treatment, as found in this study and the above‐mentioned recent study (43).…”
Section: Resultsmentioning
confidence: 97%
“…In a recent study (43) on tri and tetra cationic porphyrins, it was also shown that these porphyrins bind strongly to C. albicans cells, and the ROS, which is effective in cellular damage, is generated inside the cells. However, the microenvironment in which the yeasts are found during photosensitization can induce failure of this treatment, as found in this study and the above‐mentioned recent study (43). The effectiveness of this new mode of therapy is dependent on the protein quantity and quality in the different biological milieus (tissues or body fluids), and this must be taken into account.…”
Section: Resultsmentioning
confidence: 97%
“…Cormick et al. (53) investigated the susceptibility of C. albicans to two tetracationic porphyrins (TMPγP 4+ ) and 5,10,15,20‐tetrakis(4‐N,N,N‐trimethylammoniumphenyl)porphyrin (TMAP 4+ ) and a tricationic porphyrin 5‐(4‐trifluorophenyl)‐10,15,20‐tris(4‐N,N,N‐trimethylammoniumphenyl) porphyrin (TFAP 3+ ). All the PSs had amphiphilic character of the structure and high affinity for C. albicans .…”
Section: Photosensitizersmentioning
confidence: 99%
“…[39][40][41][42][43] Many porphyrins are lipophilic and hence should accumulate in cellular membranes but the high water-solubility of XF73 suggests localization in the cytoplasm as well. In this context it is important to have a detection procedure that provides reliable data from inside such cells, in particular when knowing that cellular constituents can substantially affect singlet oxygen luminescence.…”
Section: Discussionmentioning
confidence: 99%